Postoperative complications following intraoperative radiotherapy in abdominopelvic malignancy: A single institution analysis of 113 consecutive patients. Issue 7 (2nd March 2017) - Abdelfatah, Eihab; Page, Andrew; Sacks, Justin; Pierorazio, Phillip; Bivalacqua, Trinity; Efron, Jonathan; Terezakis, Stephanie; Gearhart, Susan; Fang, Sandy; Safar, Bashar; Pawlik, Timothy M.; Armour, Elwood; et al.
Abstract : BACKGROUND: Intraoperative radiotherapy (IORT) has advantages over external beam radiation therapy (EBRT). Few studies have described side effects associated with its addition. We evaluated our institution's experience with abdominopelvic IORT to assess safety by postoperative complication rates. METHODS: Prospectively collected IRB‐approved database of all patients receiving abdominopelvic IORT (via high dose rate brachytherapy) at Johns Hopkins Hospital between November 2006 and May 2014 was reviewed. Patients were discussed in multidisciplinary conferences. Those selected for IORT were patients for whom curative intent resection was planned for which IORT could improve margin‐negative resection and optimize locoregional control. Perioperative complications were classified via Clavien‐Dindo scale for postoperative surgical complications. RESULTS: A total of 113 patients were evaluated. Most common diagnosis was sarcoma (50/113, 44%) followed by colorectal cancer (45/113, 40%), most of which were recurrent (84%). There were no perioperative deaths. A total of 57% of patients experienced a complication Grade II or higher: 24% (27/113) Grade II; 27% (30/113) Grade III; 7% (8/113) Grade IV. Wound complications were most common (38%), then gastrointestinal (25%). No radiotherapy variables were significantly associated with complications on uni/multi‐variate analysis. CONCLUSIONS: Our institution's experience with IORT demonstrated historically expected postoperative complication rates. IORT is safe, with acceptable perioperative morbidity.